A new proof of Donoghue's interpolation theorem - Yacin Ameur (Journal of Function Spaces and Applications)
We give a new proof and new interpretation of Donoghue's interpolation theorem; for an intermediate Hilbert space H∗ to be exact interpolation with respect to a regular Hilbert couple H¯ it is necessary and sufficient that the norm in H∗ be representable in the form ‖f‖∗=(∫[0,∞](1+t−1)K2(t,f;H¯)2dρ(t))1/2 with some positive Radon measure ρ on the compactified half-line [0,∞]. The result was re-proved in [1] in the finite-dimensional case. The purpose of this note is to extend the proof given in [1] to cover the infinite-dimensional case. Moreover, the presentation of the aforementioned proof in [1] was slightly flawed, because we forgot to include a reference to ‘Donoghue's Lemma’, which is implicitly used in the proof. Hence we take this opportunity to correct that flaw.